Consideration of molecular weight-dependent high thermal resistance of end-capped-oligoimide based thermoset resins - Van-Kien Hoang; Kwak Jin Bae; Yuna Oh; Woohyeon Kwon; Jihyun Oh; Kyosun Ku; Minju Kim; Ki-Ho Nam; Jaesang Yu; Hyeonuk Yeo (Polymer Testing)
Interest in thermosetting resins for polymer applications in extreme environments, such as aerospace, is increasing. The construction of oligoimide-based crosslinking systems has been the focus of considerable research over the past 30 years, but the analysis of chemical structure and molecular weight dependence has not been systematically performed. In this study, we established both theoretical and experimental frameworks by performing simulations based on a deep understanding of the crosslinking structure and conducted a systematic investigation of the properties of bulk specimens by synthesizing and preparing samples with various molecular weights. Theoretical investigations suggested clear differences and tendencies depending on molecular weight and crosslinking reaction pathways. Furthermore, experimental results showed excellent agreement with the simulations and clearly revealed the correlation between the molecular weights of pristine resin and thermal properties, such as glass transition and decomposition. In addition, we successfully obtained a thermosetting resin with superior thermal properties under optimized conditions, including a glass transition temperature exceeding 350 °C and a decomposition temperature exceeding 570 °C.